Batch Adsorption Studies for Removal of Hg(II) from Wastewater using Syzigium jambolanum Nut Carbon - Sophie Beulah, S.; Muthukumaran, K. (Asian Journal of Chemistry, 2010)
Activated carbon prepared from Syzigium jambolanum nut was found to be useful for the removal of mercury(II) as [HgCl4]2- from wastewater. Quantitative removal of 99 % takes place when batch studies were done at an optimal carbon dose of 0.1 g, pH of 5 and equilibration time of 3 h. The adsorption follows Freundlich and Langmuir adsorption isotherms and obeys first order rate equation. The efficiency of Syzigium jambolanum carbon was compared with a commercial activated carbon.